2020
DOI: 10.1007/s11764-020-00877-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cervical cancer survivors on disability pension: a subgroup in need of attention from health care providers

Abstract: Purpose Survivors of cervical cancer have an increased risk for permanently reduced work ability qualifying for disability pension (DP). Few studies describe the social and health situation of long-term survivors of cervical cancer (LSCCs) on DP as a subgroup among LSCCs. The purpose was to investigate the socio-demographic and health status of LSCCs holding DP in a population-based cohort using LSCCs holding paid work as reference. Methods Altogether, 354 LSCCs under 67 years (age of retirement pension in Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The most common outcome of interest was employment/RTW but work ability, productivity, and other work outcomes were also examined. Similar to fatigue, approximately one-third of the studies evaluating depression and work status demonstrated significant findings [18,20,21,27,[31][32][33][34][35][36][37] but more than half of the studies evaluating work ability yielded significantly negative associations between depression and work ability [16][17][18]. In contrast, studies consistently shown non-significant findings when the association of anxiety and various work outcomes was evaluated.…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…The most common outcome of interest was employment/RTW but work ability, productivity, and other work outcomes were also examined. Similar to fatigue, approximately one-third of the studies evaluating depression and work status demonstrated significant findings [18,20,21,27,[31][32][33][34][35][36][37] but more than half of the studies evaluating work ability yielded significantly negative associations between depression and work ability [16][17][18]. In contrast, studies consistently shown non-significant findings when the association of anxiety and various work outcomes was evaluated.…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…A Swedish study [ 12 ] based on a large population-based cohort of gynaecological cancer survivors shows that cancer patients treated with radiotherapy and/or chemotherapy alone had a 1.7 times increased risk of being granted a disability pension compared with those treated with hysterectomy only. In a recent Norwegian study [ 13 ], long-term cervical cancer survivors were reported to have a two times higher prevalence of disability pension compared with females in the general population. In addition, a significantly higher proportion of cervical cancer survivors on disability pension reported treatment with pelvic radiation combined with chemotherapy compared with cervical cancer survivors in paid work [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent Norwegian study [13], long-term cervical cancer survivors were reported to have a two times higher prevalence of disability pension compared with females in the general population. In addition, a significantly higher proportion of cervical cancer survivors on disability pension reported treatment with pelvic radiation combined with chemotherapy compared with cervical cancer survivors in paid work [13].…”
Section: Disability Pensionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies have reported on the risk of negative psychological consequences after diagnosis and treatment of cervical cancer [2][3][4][5]. Also, these patients were found to have a higher risk of reduced working ability, longer sick leave, and more often holding disability pension compared with the general population in the decades after the diagnosis [6,7]. In previous studies, early and late effects were assessed after the diagnoses of cervical cancer compared with a reference group.…”
Section: Introductionmentioning
confidence: 99%